Perencanaan Analisis SWOT dalam Dunia Pendidikan di Kecamatan Sipoholon - Pardomuan Simanullang; Fajar Situmorang; Nelsa Citrayani Silaban; Riscal Boni Tamaro Sitorus; Amos Derebi; Jusni Lumbantobing (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the application of SWOT analysis as a strategic planning framework for improving the quality of education in Sipoholon District. The research problem arises from disparities in teacher competence, unequal distribution of educational facilities, and the limited use of data-driven planning, all of which contribute to uneven educational quality across schools. A descriptive qualitative approach was employed, utilizing literature review, document analysis, and synthesis of previous studies relevant to educational planning. SWOT analysis was adopted to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) that shape the educational landscape in Sipoholon. The findings reveal that institutional strengths such as teacher commitment, the presence of high-performing schools, and local government support can be optimized by leveraging external opportunities, including digital transformation policies and collaborations with partner institutions. Meanwhile, weaknesses such as insufficient digital literacy among teachers and disparities in infrastructure require evidence-based strategies tailored to local needs. The study concludes that SWOT analysis provides a comprehensive and practical foundation for designing strategic educational plans, enabling stakeholders to formulate adaptive, collaborative, and sustainable development pathways aligned with regional conditions and national education goals.